Effects of Liquid CO2 Exposure on Semi‐Crystalline Polylactic Acid. Issue 1 (February 2014) - Garancher, Jean‐Philippe; Fernyhough, Alan; Kirby, Nigel; Bulavin, Leonid; Guenet, Jean‐Michel
Summary In this work, the effect of low temperature (approximately −50°C to −20°C) liquid CO2 treatment on the morphology of semi‐crystalline polylactic acid (PLA) was studied. This investigation was carried out by means of differential scanning calorimetry (DSC) and Synchrotron wide‐angle X‐ray scattering (WAXS). Under the experimental conditions used, DSC and WAXS revealed the existence of two main crystalline structures, namely the α" crystal structure and a mesomorphic structure. The α" crystals were found to be preferentially formed at higher temperature, whereas only the mesomorphic structure was detected at lower temperature. The transition between these two morphologies was observed at around −35°C.